Rancang Bangun Alat Bedah Electric Cautery Berbasis Arduimo - Muhammad Rifqi Muwaffaq; Muslihun Muslihun; Muhammad Ulin Nuha ABA (MEDIKA TRADA, 2025)
The development of electromedical technology encourages the creation of safer and more efficient surgical tools, one of which is electric cautery. This study aims to design and build an electric cautery prototype based on an Arduino Uno microcontroller equipped with a Liquid Crystal Display (LCD) to display current (0–6 A) and frequency (0–50 Hz) parameters in real-time. The research method uses a Research and Development (R&D) approach, starting from the design stage, prototyping, to functional testing and simple clinical trials on chicken tissue. The test results show that the tool has a high level of accuracy, with a maximum relative error of 3.9% in current and 1.6% in frequency, still within the tolerance limits of the IEC 60601-2-2 standard. Simple clinical trials show that the tool is able to cut tissue well while coagulating so that the wound area remains neatly closed. These findings indicate that Arduino-based electric cautery with real-time monitoring features can be an innovative and safer alternative compared to conventional devices, although further clinical trials with stricter medical standards are still needed.